Focus-on-form and EFL learners' language development in synchronous computer-mediated communication: task-based interactions. Issue 4 (1st October 2016) - Eslami, Zohreh R.; Kung, Wan-Tsai
Abstract : The purpose of this study was to explore the occurrence of incidental focus-on-form and its effect on subsequent second language (L2) production of learners of different dyads in an online task-based language learning context. The participants included Taiwanese learners of English as a foreign language at different proficiency levels, and native speakers of English. Sixteen native speaker–non-native speaker (NS–NNS) dyads and 14 NNS–NNS dyads were formed. The dyads were asked to complete two multiphase communicative tasks in a synchronous computer-mediated communication (SCMC) environment. Language-related episodes (LREs) were identified and utilised as a basis for individualised tailor-made tests. The tailor-made post-tests were used to assess the learners' learning outcomes. The results suggested that LREs in the SCMC medium can enhance learners' language development in both dyadic types. No significant differences were found between the two dyadic types in relation to the amount of LREs produced and the learning outcomes. In sum, this quasi-experimental study demonstrates that the effectiveness of incidental focus-on-form can be measured through individualised testing of linguistic items and that research on incidental focus-on-form does not have to remain descriptive or exploratory in nature. Our findings suggest that language proficiency, dyadic type and incidental focus-on-form in the SCMC setting interacted in complex and intricate ways.